Ethno Medicinal Uses of Obnoxious Weeds from the Tribal Folklore of Pachmarhi Biosphere Reserve (Madhya Pradesh) - Kumar, Anil; Yadav, D. K. (Indian Forester, 2011)
Pachmarhi biosphere reserve is one of the richest biodiversity regions of Madhya Pradesh. Various weeds are abundant in the croplands as well as in the forests of this regions. They frequently grow on wasteland, roadsides and croplands. Aboriginals consider these plants as obnoxious weeds since these plants pose several problems in croplands and daily life. Several obnoxious weeds are highly efficacious as herbal remedies against some common ailments. In the present commnnication, ethno medicinal usages along with indigenous formulations of 35 species of weeds are documented from different ethnic group of Pachmarhi biosphere reserve (Madhya Pradesh).